The impact of kinesio taping on pain relief in patients with lateral epicondylitis: Vpliv kinezioloških trakov na zmanjšanje bolečine pri bolnikih z lateralnim epikondilitisom - Jesenšek Papež, Breda (Acta Medico-Biotechnica, 2021)
Purpose: To compare the short–term effect of kinesio taping on reducing pain in subjects with lateral epicondylitis (LE) treated with physiotherapy alone compared to physiotherapy withkinesio taping.Methods: We retrospectively reviewed the medical documentation of 188 patients diagnosed with LE and treated between January 2012 and December 2013. Ninety–five patients who were treated with the same multi–modality physiotherapy with or without kinesio taping (T0 and T1 groups, respectively) were included in our analysis. Pain intensity was measured using a visual analogue scale (VAS) before therapy and after therapy was concluded. To compare the groups, we used Student's t–test and Pearsons χ2–test. To compare the VAS score of the two groups before and after treatment, we used analysis of variance for repeated measurements. Statistical significance was set at p
Keywords: lateral epicondylitis; kinesio tape; musculoskeletal disorders